Taking the stock of granule cargo: Platelet releasate proteomics. (17th February 2017) - Pagel, Oliver; Walter, Elena; Jurk, Kerstin; Zahedi, René P.
Abstract: Human platelets are key players in a multitude of physiological and pathological processes. Upon activation they release cargo from different types of granules as well as microparticles in an apparently well-regulated and orchestrated manner. The resulting specific platelet releasates create microenvironments of biologically active compounds and proteins during platelet aggregation and thrombus formation, allowing efficient delivery of growth factors and immune modulators to their sites of effect and enhancing the coagulative response in a positive feedback loop. Thus, platelet releasates play a central role in the regulation of platelet homeostasis and heterotypic cell interaction. Additionally, it recently emerged that both the qualitative and quantitative composition of the releasate as well as release dynamics may be stimulus dependent and therefore more complex than expected. Mass spectrometry-based proteomics is an important asset for studying platelet releasates in vitro, as it allows not only (i) identifying released proteins, but moreover (ii) determining their quantities and the dynamics of release as well as (iii) differentially comparing releasates across a variety of conditions. Though owing to the high sensitivity and comprehensiveness of modern proteomic techniques, a thorough experimental design and a standardized and robust sample preparation are essential to obtain highly confident and reliable insights into platelet biology and pathology. Here, we review releasate proteome studies and crucial sample preparation strategies to summarize possible achievements of state-of-the-art technologies and furthermore discuss potential pitfalls and limitations. We provide a future perspective of platelet releasate proteomics including targeted analyses, post-translational modifications and multi-omics approaches that should be adopted by platelet releasate researchers due to their tremendous depth and comprehensiveness.